CAN MOTIVATION AFFECT THE APPLICATION OF TIME TOKEN AREND ON AQIDAH AKHLAK LEARNING IN MADRASAH IBTIDAIYAH? - Faisal Faliyandra; Evi Rizqi Salamah; Ade Eka Anggraini (International Conference on Social and Islamic Studies, 2021)
The formation of praiseworthy morals becomes a necessity education process in madrasah Ibtidaiyah, sothe learnig proccess of moral aqidah material must always apply innovative and creative learning. Thepurpose of this study looked at the relationship between the application of the arend time token learningmodel on moral aqidah material in Madrsah Ibtidaiyah (MI). and also this study will also look at whetherstudent learning motivation has a significant impact on learning models and improved student learningoutcomes at MI. To achieve the purpose of the study, experiments with an ANOVA analysis were usedtwo ways. This study sample was as many as 104 learners spread across class V MI KKM KaponganSitubondo Subdistrict. Data collection techniques for learning outcomes from students' objective testresults, while for measuring motivation using questionnaires. There are four research findings that can beexplained, namely; 1. There is a difference between students who follow the time token arend learningmodel and the conventional learning model; 2. There is an interaction between learning models andmotivation aimed at student learning outcomes; 3. For students with high motivation, there is a differencebetween the application of the time token arend learning model and the conventional learning model; 4.For students with low motivation, there are differences in the learning model of time token arend withconventional. Then overall describing the time token arend can be applied to moral aqidah learningmaterials to improve student learning outcomes in MI. Then motivation is needed so that students at MIcan follow the arend time token learning model effectively.